Energy benchmarking of manufacturing processes in foundation industries - Sarfraz, Shoaib; Sherif, Ziyad; Jolly, Mark R.; Salonitis, Konstantinos (Elsevier, 2024)
Benchmarking energy consumption and utilisation has become a crucial tool for the manufacturing sector in the drive towards sustainability. However, incorporating industrial perspectives into benchmarking efforts is necessary to identify effective and relevant metrics. This study aims to evaluate the metrics for benchmarking energy utilisation within the foundation industries by deploying two surveys while incorporating the views of industry and subject matter experts. The study also involved conducting interviews with metal foundries to investigate the energy consumption of their processes and their metrics utilisation. The findings indicate the need for an accurate and reliable method to extract values for energy benchmarking of manufacturing processes. Proper procedures must be in place to ensure the data is collected consistently and uniformly across different processes and organisations. The deployment of effective and relevant metrics through industrial prospection will help ensure the benchmarking process is meaningful, actionable and supports the goal of a more sustainable future.
56th CIRP International Conference on Manufacturing Systems 2023 (CIRP CMS 2023), 24-26 October 2023, Cape Town, South Africa
Keywords: Benchmarking; Energy Consumption; Manufacturing Process; Sustainability; Foundation Industries